Caffeic acid phenethyl ester promotes wound healing of mice pressure ulcers affecting NF-κB, NOS2 and NRF2 expression - Romana-Souza, Bruna; dos Santos, Jeanine Salles; Monte-Alto-Costa, Andréa (Life sciences (1973), 2018)
In pressure ulcers, the synthesis of reactive oxygen species induced by ischemia and reperfusion leads to chronic inflammation and tissue damage, which impair the closure of these lesions. Caffeic acid phenethyl ester (CAPE), found in propolis, promotes cutaneous wound healing of acute lesions and severe burns. However, the effects of CAPE on wound healing of pressure ulcers have not been investigated. This study investigated the effects of CAPE administration in a murine model of pressure ulcers. To induce pressure ulcers, two cycles of ischemia and reperfusion by external application of two magnetic plates were performed in the skin dorsum of mice. After the last cycle, animals were treated daily with CAPE or vehicle until they were euthanized. The nitric oxide synthesis, lipid peroxidation, macrophage migration, protein nuclear factor kappa B and nitric-oxide synthase-2 expression were increased 3 days after ulceration but decreased 7 days later, in pressure ulcers of the CAPE group compared to that of the control group. CAPE reduced the protein expression of nuclear factor-erythroid2-related factor 2 in pressure ulcers 3 days after ulceration, but increased 7 days later. Myofibroblast density was increased in the CAPE group 7 days after ulceration, but reduced 12 days later when compared to control group. In addition, CAPE promoted collagen deposition, re-epithelialization and wound closure of mice pressure ulcers 12 days after ulceration. CAPE brings forward inflammatory response and oxidative damage involved in injury by ischemia and reperfusion, promoting dermal reconstruction and closure of pressure ulcers.